COVID-19 pandemic: consequences of overexposure to the use of information and communication technologies - Ortiz-León, María Cristina; Gómez-Ramos, Rebeca Guadalupe; Arguelles-Nava, Vianey Guadalupe; López-Zetina, Javier; Pavón-León, Patricia; Ortiz-Chacha, Christian Soledad (Horizonte Sanitario, 2024)
Objective: We aimed to analyze the association between overexposure to the use of ICT with the perception on healthy lifestyles and mental health before and during the pandemic. Materials and methods: We conducted a quantitative and retrospective cohort study on students from 3 high schools, located in the Gulf of Mexico, who were surveyed using an online questionnaire. Descriptive statistics, such as measures of central tendency and dispersion, were used to analyze the results. Also, statistical techniques were used for related samples to specify changes occurred before and during the pandemic. The Odds Ratio and its 95% confidence intervals were calculated to identify the association between overexposure to the use of ICT with healthy lifestyles and mental health. Results: 432 students were included in our study. Most of them were female (66.7%), (62.7%) were studying the second semester, aged 15 (39.4%) to 16 (35.6%) years. Regarding the use of ICT, we found that before the pandemic more than 50% of the responses pointed out a normal use, but during the pandemic the use of various devices increased. Concerning the association between overexposure to the use of ICT and mental health, in this case depression, we found that before the pandemic students had almost 2.9 times the chance of developing depression if they had been overexposure to the use of ICT. These possibilities increased almost 7.2 times during the pandemic. Conclusions: Further research is mandatory to explore the mental health of adolescents, since during the COVID-19 pandemic important changes occurred, including those changes inherent to the stage they are undergoing.